Prueba piloto de un software para el telemonitoreo de signos vitales en pacientes COVID-19 de la UCI del Centro Médico Crecer (2021)
The global health crisis due to coronavirus (COVID-19) appeared at the end of 2019 (WHO, 2021) in an unexpected way before the world, leaving health personnel at the forefront of risk. This is why the Intensive Care Unit (ICU) of the Crecer Medical Center has adapted to face this global health crisis. However, access to information on the vital signs of patients has affected medical and care personnel, due to exposure due to direct contact between patient-doctor. For this reason, the objective of this project is to carry out a pilot telemonitoring software, which allows the visualization of vital signs (oxygen saturation, temperature, non-invasive blood pressure and heart rate), which will be displayed through a mobile application that was carried out in three phases. First, the software was designed to obtain data from the vital signs monitor, it should be said that to obtain data, the vital signs monitor was used in DEMO mode. In the second instance, a user interface was designed to visualize the data obtained, and, finally, a module was created that shows the alarms when the patient has alterations outside the normal range, in which the values in the graph were altered to be able to cause the alarm since the DEMO mode does not have the vital signs of patients in critical condition.